The Role of Psychological Empowerment in Linking Paradoxical Leadership to Nurses’ Workplace Thriving - Abou Zeid, Mennat Allah G.; Ibrahim, Ibrahim Abdullatif (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Paradoxical leadership, characterized by balancing competing yet interrelated managerial demands, such as maintaining managerial control while simultaneously allowing nurses’ professional autonomy, has emerged as a promising leadership approach in complex healthcare environments. However, empirical evidence regarding how paradoxical leadership relates to positive psychological outcomes, such as psychological empowerment and workplace thriving, remains limited in nursing research, particularly within Middle Eastern healthcare contexts.Purpose: This study examined the association between paradoxical leadership and workplace thriving among nurses and explored the potential mediating role of psychological empowerment. Methods: A cross-sectional correlational study was conducted using a convenience sample of 231 nursing staff from three tertiary hospitals. Data were collected through a web-based survey that included the Paradoxical Leadership Behavior Scale, Psychological Empowerment Scale, and Thriving at Work Scale, along with demographic information. Structural equation modeling using the partial least squares approach was applied to examine the hypothesized relationships.Results: Nurses reported moderate levels of paradoxical leadership (M = 3.12, SD = 0.44), psychological empowerment (M = 4.37, SD = 0.69), and workplace thriving (M = 3.45, SD = 0.45). Paradoxical leadership was positively associated with psychological empowerment (β = 0.720, p < .001) and workplace thriving (β = 0.553, p < .001). Psychological empowerment was also positively associated with workplace thriving (β = 0.336, p < .001). Mediation analysis indicated a significant indirect association between paradoxical leadership and workplace thriving through psychological empowerment (β = 0.241, p < .001), suggesting a partial mediation pattern consistent with the proposed model.Conclusion: Paradoxical leadership was positively associated with nurses’ workplace thriving both directly and indirectly through psychological empowerment. These findings highlight the potential relevance of leadership practices that balance competing managerial demands in supporting nurses’ positive work experiences. Leadership development initiatives that foster empowering leadership behaviors may help strengthen nurses’ engagement and thriving within healthcare organizations.